Implementasi MADM TOPSIS dalam Pemilihan Karyawan Baru pada PT Arthawenasakti Gemilang Berbasis Web - Septarini, Ri Sabti; Taufiq, Rohmat; Handayani, Nurdiana; Asy’arie, Zain Ibrahim (Jurnal Informatika Universitas Pamulang, 2021)
Recruiting new employees is the process of selecting potential employees to attract talented employees who will join the company later. Improve your company's productivity by hiring new employees who meet your company's standards. In addition to the development of information and communication technology, it is considered necessary to use a decision support system for recruiting new employees to facilitate the management process in the selection of new employees. One of the decision support system methods that can be used in the potential employee selection process is the Order Preference Method (TOPSIS), which resembles an ideal solution. In this study, we developed system applications using PIECES system analysis techniques, system development techniques using waterfall models using Unified Modeling Language (UML) models, application development using Sublime, and devices using black boxes. Describes the test. The end result of hiring an employee using a decision support system provides managers with hiring recommendations and is already available as a web-based hiring system.